2023
DOI: 10.3390/biology12071029
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antioxidant Compounds in Fruits of Citrus reticulata Blanco Using Postharvest LED Irradiation

Abstract: Phlegrean mandarin fruits are already known for health-promoting properties due to the high concentration of phytochemicals in peel, pulp, and seed. Biotic and abiotic factors, including light, may modulate their biosynthesis, metabolism, and accumulation. In this context, light-emitting diodes (LED) have recently been applied to control nutritional traits, ripening process, senescence, fruit shelf-life, and pathogenic microbial spoilage of fruits. This study investigated the effect of the seven-day exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We can assume, as reported in [19], that compounds contributing to the antioxidant activity of RB extracts include some phenolics, namely flavones, flavanols, anthocyanidins, benzoic and cinnamic acids, which at specific concentrations-in our case, 1 µg/mL-may contrast and/or mitigate the DNA damage and the oxidative-induced genotoxicity. Identify-ing a method to boost such compounds in plant crude extract is worthy of attention because these molecules have powerful antioxidant, anti-inflammatory, and anti-cancer activity.…”
Section: Inizio Modulomentioning
confidence: 85%
See 3 more Smart Citations
“…We can assume, as reported in [19], that compounds contributing to the antioxidant activity of RB extracts include some phenolics, namely flavones, flavanols, anthocyanidins, benzoic and cinnamic acids, which at specific concentrations-in our case, 1 µg/mL-may contrast and/or mitigate the DNA damage and the oxidative-induced genotoxicity. Identify-ing a method to boost such compounds in plant crude extract is worthy of attention because these molecules have powerful antioxidant, anti-inflammatory, and anti-cancer activity.…”
Section: Inizio Modulomentioning
confidence: 85%
“…More specifically, as described by [19], RB light regimes increased the concentration of some flavones, flavanols, anthocyanidins, and benzoic and cinnamic acids in citrus fruits compared to W regime. The more specific qualitative analysis of the phenolic profile in fruits showed that RB light boosted some phenolic substances such as sinensetin, linarin, caffeic, ferulic, and vanillic acids, known for their anti-inflammatory, antimicrobial, cardioprotective, anticancer, and antidiabetic properties.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…These flavor attributes and health-promoting properties are attributed to phytochemicals, including sugars, organic acids, flavonoids, limonoids, and terpenes [4]. The phytochemical profiles of citrus fruits depend on numerous factors, including the variety [5], growing region [6], postharvest treatment [7], storage conditions [8], and environmental growing conditions [2]. Factors such as the cultivation method, lighting conditions, fertilization, temperature, and soil moisture markedly affect the phytochemical profiles of citrus fruits [9][10][11].…”
Section: Introductionmentioning
confidence: 99%